A Case Report of Suspected Tuberculous Granuloma in the Kidney after BCG Perfusion Therapy for Urothelial Carcinoma of the Renal Pelvis - Kobayashi, Shin (Hinyokika kiyo. Acta urologica Japonica, 2016)
A 66-year-old male patient was referred to our hospital for bilateral renal pelvic tumors. Ureteroscopic biopsy revealed urothelial carcinoma (UC) of low grade (G1) of the renal pelvis. Renal sparing treatment with systemic chemotherapy and percutaneous tumor resection was performed. However, during subsequent follow up, a recurrent tumor was found on the left ureter. After ureteroscopic laser ablation of the tumor, Bacillus Calmette-Guerin (BCG) perfusion therapy (once a week, total 6 weeks) was performed via a single J ureteral catheter with no adverse events. Later, another recurrent recurrence was found on the right ureter, and was managed by ureteroscopic laser ablation followed by BCG perfusion therapy via a single J ureteral catheter. However, the patient developed high fever with chill from the day after initial BCG perfusion therapy on the right side. Although we started antibiotics, high fever continued. Then antituberculous drugs were administered and his condition was improved. Computed tomographic scan revealed a right renal mass 57 mm in diameter, which was consistent with tuberculous granuloma. The tuberculous granuloma persisted despite the continuation of anti-tuberculous drugs. In exceptional cases of upper tract UC such as single kidney and bilateral tumor, BCG perfusion therapy has been used as adjunctive treatment to cure or prevent UC. However, dosages and administration methods of BCG perfusion therapy for upper tract UC still remain to be standardized. Serious adverse events after BCG perfusion therapy require prompt and proper management including the use of anti-tuberculous drugs